Nilai-Nilai Spiritualitas dalam Aksi: Kepemimpinan di Yayasan Dompet Dhuafa - Isqowi Indhadhin; Mukrodi Mukrodi; Hadi Supratikta (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This study explores the application of spirituality-based leadership within the context of a philanthropic organization, focusing on the integration of spiritual values such as honesty, justice, discipline, humility, and openness to change. Utilizing a qualitative case study approach, the research was conducted through interviews and observations at a leading philanthropic foundation. The findings reveal that spiritual values are effectively integrated into leadership practices, contributing to increased organizational integrity, accountability, and productivity. Honesty and justice in decision-making strengthen employee trust and commitment, while openness to change and discipline support adaptation and the effectiveness of the work culture. The humility of leaders creates a conducive and egalitarian work environment, fostering collaboration and job satisfaction. These findings highlight the importance of spirituality-based leadership in reinforcing the ethical and spiritual identity of the organization, as well as enhancing its operational effectiveness.